1998
DOI: 10.1021/om980213l
|View full text |Cite
|
Sign up to set email alerts
|

Bromination of Os3(CO)11(EPh3) (E = P, Sb): Unexpected Formation of a Tandem Donor−Acceptor Metal Chain

Abstract: Bromination of the substituted triosmium clusters Os3(CO)11(EPh3) (E = P, Sb) yielded two trimetallic chain compounds, viz., (Br)2Os(CO)3Os(CO)4Os(CO)4(EPh3) and (Br)(OC)4OsOs(CO)4Os(CO)3(Br)(EPh3). The former contains two donor−acceptor metal−metal bonds in tandem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…To appreciate the potential diversity of structure and bonding for phosphorus, Fig. 1 presents classic Lewis representations for each possible coordination number (1)(2)(3)(4)(5)(6). Many of these 'bonding environments' have been observed in stable compounds, including those involving pπ-bonding with phosphorus.…”
Section: Bonding Environments For Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…To appreciate the potential diversity of structure and bonding for phosphorus, Fig. 1 presents classic Lewis representations for each possible coordination number (1)(2)(3)(4)(5)(6). Many of these 'bonding environments' have been observed in stable compounds, including those involving pπ-bonding with phosphorus.…”
Section: Bonding Environments For Phosphorusmentioning
confidence: 99%
“…Reports of metal complexes behaving as ligands towards other metals 4 introduce new synthetic opportunities and novel bonding possibilities. In a similar context, electron-rich phosphine centres are observed to behave as Lewis acceptors exhibiting structural diversity that requires evolution of the simple bonding models for more general applicability.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, it has been demonstrated that the bromination of Os 3 (CO) 12 did not proceed via the bromonium cluster [Os 3 (CO) 12 (μ-Br)] + , which was isolated from the reaction of Os 3 (CO) 12 with Br + , while the bromination of Os 3 (CO) 11 (PPh 3 ) gave products which suggested a bromonium cluster intermediate, the structure of which has not been confirmed . The isolation and characterization of the compounds 2 here therefore constitute the first direct verification for the bromonium mechanism in the bromination of clusters.…”
Section: Resultsmentioning
confidence: 68%
“…It has recently been shown that the reaction of Br + with the parent carbonyl cluster Os 3 (CO) 12 gave the bromonium cluster [Os 3 (CO) 12 (μ-Br)] + , and it was also demonstrated that this cluster was not the intermediate involved in the direct bromination reaction . In contrast, we have recently reported that the bromination of the substituted clusters Os 3 (CO) 11 (EPh 3 ) (E = P, Sb) gave two isomeric products, (Br) 2 Os(CO) 3 Os(CO) 4 Os(CO) 4 (EPh 3 ) and (Br)(OC) 4 OsOs(CO) 4 Os(CO) 3 (Br)(EPh 3 ) and suggested that the intermediate was a bromonium cluster with a terminal Br atom …”
Section: Introductionmentioning
confidence: 98%
“…The present study reports a synthetic route to new Pt−Pt−M (M = Rh, Ir) heterotrimetallic clusters with d 9 −d 9 −d 8 metal combination, the T-shaped linear clusters 6 , [Pt 2 {MClL}(μ-dpmp) 2 L] 2+ , and the asymmetrical A-frame clusters 7 , [Pt 2 {M(μ-Cl)L}(μ-dpmp) 2 L] 2+ (L = XylNC). In particular, the coordinatively unsaturated 3:2:4 type clusters 6 with 44 valence electrons are interesting concerning their reactivity, and the linearly ordered Pt 2 M structures with Pt−Pt covalent and Pt←M dative bonds are unprecedented, whereas Liu et al recently reported the linear Os 3 cluster containing tandem metal−metal dative bonds . Complex 6 reacted with isocyanide molecules to afford the linearly ordered 3:2:5 type clusters [Pt 2 {MXL 2 }(μ-dpmp) 2 L] n + ( 8a , M = Rh, L = XylNC, X = Cl, n = 2; 9a , M = Rh, L = X = XylNC, n = 3; 9b , M = Ir, L = X = MesNC, n = 3).…”
Section: Discussionmentioning
confidence: 99%